The impacts of female insertion in the labor market on the nutritional profile and the eating habits of adolescent students (Research, Society and Development, 2021)
Innumerable factors justify the increase in the number of cases of overweight and obesity among the Brazilian population in the latest decades, including the insertion of women in the labor market, a reality that alters the family structure and the nutrition models, mostly for children and adolescents. The present research aims to evaluate the impacts of female insertion in the labor market on the nutritional status of adolescent students, analyzing the anthropometric profile and the eating habits of 67 high-school students from the 1st to the 3rd grade of a full-time public school from the city of Fortaleza/CE. This evaluation was made possible by the application of a validated questionnaire with the students and by reading their anthropometric data, based on the World Health Organization (WHO) growth curves reference charts, in which these values were correlated with age and gender of the volunteers and converted into z-scores. Therefore, it can be seen that 53.8% of students diagnosed with overweight have their mothers in the labor market, 80% of the obese students appear among the group of families supported by the mother and 50% of those who have been diagnosed with severe obesity are among the adolescents provided by the maternal figure. Thus, it is considered that women still play the role of caregiving in the family context and that it is urgent to implement actions of Food and Nutrition Education in schools in the sense of promoting healthy eating practices among students by means of their autonomy development.